STUDENTS’ PERCEPTION OF RPP DESIGN AND USE OF LEARNING MEDIA THROUGH THE MICRO-TEACHING PRACTICE - Yuri Lolita; Sumarniningsih; Henny Dwi Iswati; Nur Fauzia (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2022)
The aims of this research are 1) The students’ the teaching practice in microteaching, 2)The students’ perception of the Lesson Plan design in microteaching practice, 3) Students’ perception of the use of learning media in microteaching practice. This method of this research was use descriptive qualitative. Subject of the Research is the location of this research was at English Department, Universitas Negeri Surabaya. The subject of the research was the students at Universitas Negeri Surabaya, English Department of seventh semester. The researcher observed one classes consists of 87 students. Based on the data obtained, the researcher concludes that most of the students gave positive perceptions of the microteaching practice in the teaching and learning process, there were many statements that microteaching got a lot of knowledge, including how to teach properly and correctly, and microteaching can to increase self-confidence and being more excited.